REFLEKSI FEMINISME DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - tri indri astuti (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2021)
Discussions about gender equality and feminism are always interesting topic to discuss. This phenomenon of gender imbalance or inequality often occurs in social life. Women receive subordinate treatment compared to men. Often the discriminatory treatment is raised through various literary works, such as novels. This research will discuss about the issue of feminism raised by a well-known author in Indonesia, Andrea Hirata, in her latest novel entitled Guru Aini. The research design is using qualitative descriptive.